Factors for Pricing Decision of Food Products in Mbeya City, Tanzania - Mwidege, Asheri M. (PAN-AFRICAN JOURNAL OF BUSINESS MANAGEMENT, 2023)
This study examined factors in the pricing decision of food products in Mbeya City. It employed non- experimental research design where every participant had an equal chance of being selected in which a sample of 100 food vendors through a cross-sectional time dimension was collected using questionnaires at Mwanjelwa, SIDO, and Soweto markets in Mbeya City. Multiple regression techniques were employed in data analysis using both SPSS and STATA packages. Variable inflationary factors and link tests were used to predict multi-collinearity and model specification. Findings showed that dependents of food dealers were inversely correlated with the pricing of food products. Furthermore, the income level of customers was inversely related to the price of food products while the type of customers and customer beliefs were both positively related to the price of food. Study concluded that vendors’ dependents, income level of customers, type of customers, and customer beliefs on food vending services influence the pricing decision of food products. It is, therefore, recommended that local government authorities should empower food dealers on pricing decision of food products and services.